Dezvoltarea serviciilor sociale adresate persoanelor vârstnice în România: contribuţia fondurilor europene - Stănculescu, Manuela Sofia; Marin, Monica (Calitatea Vieții, 2019)
This paper analyzes the European-funded projects developing social services for the elderly in Romania, implemented in the programming period of 2007–2013. The analyses included in the study are based on a desk research and a secondary analysis of data published by the Ministry of European Funds. In addition, a census of projects funded by the Regional Operational Program (POR) contracted by public institutions and including objectives about elderly people was carried out. This latter data source shows that social services for the elderly funded by European funds are mainly located in the urban area. By development region, most of the contracts are located in the North-East and South-East development regions. Municipalities with a high fiscal capacity absorbed most of the European funds aimed at social services for the elderly, with the Regional Operational Program of 2007–2013. Regarding administrative capacity, most of the municipalities with this type of projects had by the end of 2009 specialized personnel – at least one person trained in drafting European funded projects. Sustainability of social services for the elderly people is problematic especially for the municipalities with a low fiscal capacity, but also for institutions at county level. The public institutions developing social services for the elderly funded by European projects recommend conducting studies for a better knowledge and adjustment of projects to the needs of the elderly people.